Removal of Hydrogen Sulfide by Physico-Biological Filtration Using Dried Activated Sludge and Rice Husk Silica - Mehdinia Choubi, Seyed Mahmoud (2011)
The main goal of this study was to determine the effectiveness of mixed rice husk silica with dried activated sludge as a packing material for physico-biological filter for removal of hydrogen sulphide (H2S). Removal efficiency (RE), elimination capacity (EC), and pressure drop were used to show the performance of the filters. Three separate filters (physical, biological, and physico-biological filters) were built using PVC cylinder (packed to one litter). Rice husk silica, dried activated sludge and mixture of rice husk silica with dried activated sludge were used in these physical, biological and physico-biological filters, respectively. In this study, the system was operated under different conditions of two parameters, namely different inlet gas concentration and different inlet gas flow rate. The inlet and outlet concentrations of H2S were measured using H2S detector model ppb RAE 3000, USA. In order to determine the characteristics of rice husk silica, the Brunauer-Emmett Teller (BET) specific surface area was performed using a ThermoFinnigan Sorptomatic apparatus and nitrogen adsorption at -196°C. Both the shape and pores of rice husk silica were studied using scanning electron microscope (SEM). The BET method showed that rice husk silica has a very high surface area (226.3 m2/g) with a median pore radius of 2.4 nm and a mesoporous structure. Meanwhile, the chemical composition analysis showed that rice husk silica consisted up to 97.35 % of SiO2. The physico-biological filter showed more than 99.96 % RE with empty bed residence time (EBRT) of 45 to 90 sec and 300 ppm inlet concentration of H2S. However, the RE decreased to 96.87 % with the EBRT of 30 s. In the same condition, the biological filter showed 99.37% RE. Nonetheless, the RE was shown to have dropped to 82.09 % with the EBRT of 30 s. The physical filter showed an average RE of 45.83 % with EBRT of 75 to 90 s, and it was saturated after 13 days of operating time with 300 ppm inlet concentration of H2S. The maximum EC was obtained in the physico-biological filter up to 52.32 gm-3h-1, with the RE of 96.87% and H2S mass loading rate of 54 gm-3h-1. The maximum EC in the biological filter was obtained up to 44.33 gm-3h-1 with the RE of 82.09% and the H2S mass loading rate of 54 gm-3h-1. In the physical filter, on the contrary, the maximum EC was obtained only up to 11.47 gm-3h-1 with the RE of 62.41% and the H2S mass loading rate of 18.36 gm-3h-1. After 53 days of operating time and 54 gm-3h-1 of mass loading rates, the maximum pressure drop reached to 3.0 and 8.0 (mm H2O) for the physico-biological and biological filters, respectively. Nevertheless, the pressure drop did not increase in the physical filter in the same condition. In biological and physico-biological filters, there is a direct and very high relationship between the increase of the H2S mass loading rate and the amount of pressure drop (r= 0.98, p< 0.01) and (r= 0.96, p< 0.01), respectively. Based on the findings of this study, mixed rice husk silica and dried activated sludge could be considered as suitable packing material for the physico-biological filter to remove H2S.